ANALISIS KONDISI HYGIENE SANITASI PEMONDOKAN DAN KELUHAN KESEHATAN KULIT DI PANTI ASUHAN AL-JAM’IYATUL WASHLIYAH PULO BRAYAN TAHUN 2015 - kiki agusty; indra chahaya; taufik ashar (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Hygiene is very important and must be considered as it will affect the health and psychological state of a person. A clean and healthy environment will have an effect on the skin. Unsanitary environment can give rise to complaints about the health of the skin. In addition, personal hygiene also contributes greatly to skin health. The aim of this study was to determine the conditions of hygiene and sanitation as well as complaints about the health of the skin at the Orphanage Al-Jam'iyatul Washliyah in Pulo Brayan, Medan. The current research is using descriptive method. Total population in this study was 356 and taken a sample of 78. Samples were taken using stratified sampling method by quota sampling. The study results showed that the respondents who have a complaint about the health of skin totaling  28 person (35.9%), dominated by male respondents 15 respon (19.2%) and the education level of the MTS as much as 18 (23%). And sanitary conditions meet the criteria for a healthy home. Skin health complaints experienced by the santri are due to factors that are less good personal hygiene. The study results also showed that the cleanliness of the bed and bed linen are in bad condition reported by 28 subjects (35.9%). In addition, the lack of awareness for the drying bed was reported by 16 subjects (20.5%). As a conclusion from this study is that the complaints about the health of the skin are found in Orphanage Al-Jam'iyatul Washliyah in Pulo Brayan, Medan. Therefore, it is recommended that santri pay more attention to personal hygiene such as cleanliness of the skin, hands, feet, hooves, genitalia, towels, clothing, bedding, bed linen, and hair.   Keywords: Personal Hygiene, Dormitory Sanitation, Skin